The dominant leg is more likely to get injured in soccer players: systematic review and meta-analysis. - DeLang, Matthew D.; Salamh, Paul A.; Farooq, Abdulaziz; Tabben, Montassar; Whiteley, Rodney; van Dyk, Nicol; Chamari, Karim (Biology of Sport, 2021)
In soccer (football), dominant limb kicking produces higher ball velocity and is used with greater frequency than the non-dominant limb. It is unclear whether limb dominance has an effect on injury incidence. The purpose of this systematic review with meta-analysis is to examine the relationship between limb dominance and soccer injuries. Studies were identified from four online databases according to PRISMA guidelines to identify studies of soccer players that reported lower extremity injuries by limb dominance. Relevant studies were assessed for inclusion and retained. Data from retained studies underwent meta-analyses to determine relative risk of dominant versus non-dominant limb injuries using random-effects models. Seventy-four studies were included, with 36 of them eligible for meta-analysis. For prospective lower extremity injury studies, soccer players demonstrated a 1.6 times greater risk of injury to the dominant limb (95% CI [1.3–1.8]). Grouped by injury location, hamstring (RR 1.3 [95% CI 1.1–1.4]) and hip/groin (RR 1.9 [95% CI 1.3–2.7]) injuries were more likely to occur to the dominant limb. Greater risk of injury was present in the dominant limb across playing levels (amateurs RR 2.6 [95% CI 2.1–3.2]; youths RR 1.5 [95% CI 1.26–1.67]; professionals RR 1.3 [95% CI 1.14–1.46]). Both males (RR 1.5 [95% CI 1.33–1.68)] and females (RR 1.5 [95% CI 1.14–1.89]) were more likely to sustain injuries to the dominant limb. Future studies investigating soccer injury should adjust for this confounding factor by using consistent methods for assigning limb dominance and tracking use of the dominant versus non-dominant limb.